On the convergence of the sums of the Markov renewal processes to a many-dimensional Poisson process - Sapagovas, J. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. Сапаговас. О сходимости сумм марковских процессов восстановления к многомерному процессу Пуассона J. Sapagovas. Apie Markovo atstatymo procesų sumų konvergenciją į daugiamatį Puasono procesą